Perception of Nursing Work Satisfaction in Patient Safety Culture - Titi Purwani; Fahmi Rahmy; Zifriyanthi Minanda Putri (International Journal of Science and Society, 2020)
Health service mistakes can result in thousands of people dying annually. One strategy to improve patient safety is to create the safety culture of patients with the satisfaction of nursing work. The dissatisfaction of nurses work can lead to a decline in hospital service quality. Objective: This study aims to know the relationship perception of nurse work satisfaction to patient safety culture. The studies used are descriptive-analytic with a cross-sectional approach. The sample number of 137 nurses taken at Padang in the 2020 period with total sampling techniques. There is a significant link between salary satisfaction, supervision, additional benefits, motivation, technical procedures, communication, and nursing work satisfaction with the safety culture of the patient. The most significant relationship is supervision with the safety culture of the patient.